Implementation of Flipped Classroom in Increasing Students’ Grammar Ability of Islamic Economic Department Student in UIN Datokarama Palu - Mansur, Nurfauziah; Fatima, Fatima; Rengur, Zul Aini (Jurnal Pendidikan dan Pembelajaran Indonesia (JPPI), 2024)
The aim of this research was to describe the effect of the flipped classroom on increasing students’ ability in grammar. This research belonged to quasi-experimental research with a group pre-post-test design involving 50 bachelor degree students from the Islamic Economic Department at UIN Datokarama Palu as the sample. The sampling technique was total sampling with the experimental group (25 students) and control group (25 students). To assess the students’ ability in grammar, four components were measured: accuracy in tense usage, consistency, understanding of tense form, and contextual appropriateness. The students’ scores were classified into five categories: very good, good, medium, low, and failed. After treatment, the grammar ability scores increased for the experimental group. The percentage increased in all aspects: accuracy in tense usage increased by 45%, consistency by 40.6%, understanding of tense form by 31%, and contextual appropriateness by 32.8% from the pre-test scores. The Flipped Classroom model revolutionized the teaching of English grammar, offering practical strategies for implementation, and emphasizing the need for collaborative and independent learning experiences to enhance students' language proficiency and overall learning outcomes.